Environmental effect on the load-dependent friction behavior of a diamond-like carbon film. (February 2015) - Cui, Longchen; Lu, Zhibin; Wang, Liping
Abstract: We examine the influence of gaseous atmospheres and applied loads on the friction behaviors of a low-hydrogenated diamond-like carbon (DLC) film. The results show that friction behaviors of the DLC film can be manipulated by adjusting the contact stress in conjunction with the test atmosphere, particularly the humidity. By this way, surprisingly, the low-hydrogenated DLC film is enabled to display a superlow friction coefficient (~0.003) with a long wear life (>20000 sliding cycles). The mechanical and mechanochemical effects of the contact stress and the effect of humidity on the friction behaviors of the DLC film are elaborately discussed. Highlights: ● Effects of atmosphere and load on the friction behavior of a DLC film are studied. ● The DLC film is a low-hydrogenated one with H content about 7.86 at.%. ● The film can show a superlow friction coefficient (0.003) in a specific condition. ● Friction mechanisms underlying the environment- and load-dependence are discussed.